Effect of methylene blue on hemodynamic and metabolic response in septic shock patients. Issue 3 (21st January 2022) - Luis-Silva, Fabio; Menegueti, Mayra Gonçalves; Sepeda, Corina dos Reis; Petroski-Moraes, Bruno C.; Sato, Lucas; Peres, Leandro Moreira; Becari, Christiane; Basile-Filho, Anibal; Evora, Paulo R.B.; Martins-Filho, Olindo Assis; Auxiliadora-Martins, Maria
Abstract: Introduction: Septic shock is a lethal disease responsible for a large proportion of deaths in the Intensive Care Unit (ICU), even with therapy centered on fluid resuscitation, use of vasopressors and empirical antibiotic therapy applied within the first hour of diagnosis. Considering the multifactorial pathophysiology of septic shock and the mechanism of action of vasopressors, some patients may not respond adequately, which can lead to the maintenance of vasodilatation, hypotension and increased morbidity, and mortality. This protocol aims to verify whether the use of methylene blue in septic patients with an early diagnosis can contribute to an earlier resolution of a shock compared to standard treatment. Methods and analysis: This is a study protocol for a single-center randomized clinical trial design in an ICU of a tertiary university hospital. In this study, we intend to include 64 patients aged between 18 and 80 years with a diagnosis of septic shock, of any etiology, with up to 72 hours of evolution after volume restoration, using norepinephrine at a dose ≥0.2 μg/kg/min and vasopressin at a dose of 0.04 IU/min. After the initial approach, we will randomize patients into two groups, standard care, and standard care plus methylene blue. The sample size was calculated in order to show 30% differences in septic shock resolution between groups. The Research Ethics Committee approved the study, and all patients included will sign an informed consent form (Clinical registration: RBR-96584w4).